2018
DOI: 10.17235/reed.2018.5822/2018
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage versus single-stage procedure for the management of cholecysto-choledocholithiasis in elderly patients: a retrospectively cohort study

Abstract: Background: there is an increasing incidence rate of cholecysto-choledocholithiasis associated with the increasing proportion of senile individuals. Methods: a total of 100 elderly patients (over 80 years of age) suffering both from cholelithiasis and choledocholithiasis were retrospectively studied from January 2010 to December 2016. Patients were scheduled for either a single-stage or two-stage procedure. The LCBDE group (n = 54) included cases that underwent a single stage procedure of laparoscopic explorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…In the present study, the overall incidence of postoperative complications was 15.9% in the elderly group and 3.9% in the young and middle-aged group, including surgical site infections, bleeding, bile duct injuries, and respiratory issues, and the difference was statistically significant. Zhang et al [ 22 ] reported an overall incidence of complications of 18.5% in elderly patients undergoing LC + LCBDE, and Zhou et al [ 8 ]reported an incidence of 14.8%, which was consistent with the findings of the present study. In the present study, pulmonary infection was the major and most common complication in these elderly patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the overall incidence of postoperative complications was 15.9% in the elderly group and 3.9% in the young and middle-aged group, including surgical site infections, bleeding, bile duct injuries, and respiratory issues, and the difference was statistically significant. Zhang et al [ 22 ] reported an overall incidence of complications of 18.5% in elderly patients undergoing LC + LCBDE, and Zhou et al [ 8 ]reported an incidence of 14.8%, which was consistent with the findings of the present study. In the present study, pulmonary infection was the major and most common complication in these elderly patients.…”
Section: Discussionsupporting
confidence: 92%
“…The currently known methods include ERCP + LC and LC + LCBDE [ 3 7 ]. However, ERCP is associated with postoperative complications due to a damaged SO [ 8 , 9 ] and increased difficulties in selective LC. Accordingly, LCBDE combined with LC can enable surgeons to address the two conditions at the same time while patients are anaesthetised only once, maximising the interests of patients with a higher success rate and lower postoperative recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…However, this difference in the complication rates may be attributed to the fact that only studies that set the age limit as 65 or 70 years were included. The complication rate was similar to that reported in a previous study that included patients aged >80 years (14.8%) [23].…”
Section: Discussionsupporting
confidence: 89%
“…However, for common bile duct stones, it is still a matter for debate. An increasing number of studies describe the benefits of one-stage treatment for gallstones combined with CBD stones using minimally invasive surgery instead of ERCP combined with LC [ 19 , 20 ]. For patients with a history of previous gastrectomy with gastrojejunostomy, ERCP and LCBDE were both possible solutions for CBD stones [ 21 ].…”
Section: Discussionmentioning
confidence: 99%